Carbene‐Mediated Functionalization of the Anomeric CH Bond of Carbohydrates: Scope and Limitations. Issue 19 (18th February 2013) - Boultadakis‐Arapinis, Mélissa; Prost, Elise; Gandon, Vincent; Lemoine, Pascale; Turcaud, Serge; Micouin, Laurent; Lecourt, Thomas
Abstract Herein we investigate the scope and limitations of a new synthetic approach towards α‐ and β‐ketopyranosides relying on the functionalization of the anomeric CH bond of carbohydrates by insertion of a metal carbene. A key bromoacetate grafted at the 2‐position is the cornerstone of a stereoselective glycosylation/diazotransfer/quaternarization sequence that makes possible the construction of a quaternary center with complete control of the stereochemistry. This sequence shows a good tolerance toward protecting groups commonly used in carbohydrate chemistry and gives rise to quaternary disaccharides with good efficiency. In the case of a disaccharide with a more restricted conformation, this functionalization process can be hampered by the steric demand next to the targeted anomeric position. In addition, the formation of transient orthoesters during the glycosylation step may also reduce the overall efficiency of the synthetic sequence.